Asian Ethnology (JSTOR)
Asian Ethnology seeks to deepen understanding and further the pursuit of knowledge about the peoples and cultures of Asia. We wish to facilitate intellectual exchange between Asia and the rest of the world, and particularly welcome submissions from scholars based in Asia. The journal presents formal essays and analyses, research reports, and critical book reviews relating to a wide range of topical categories, including narratives, performances, and other forms of cultural representation; popular religious concepts; vernacular approaches to health and healing; local knowledge; collective memory and uses of the past.
Keywords: Asian Studies